Border Poetics: Gender, Essayism and Border Crossing in Sinéad Gleeson’s Constellations: Reflections from Life - Terrazas Gallego, Melania (Miscelánea: A Journal of English and American Studies, 2022)
As Julie Bates claims, “the most exciting new writing in Ireland is happening in the field of nonfiction” (2020: 228-229) and, more particularly, in the form of the essay. Sinéad Gleeson uses the confessional mode in her essay collection Constellations: Reflections from Life (2019) to recount her experiences of two deadly illnesses and to challenge ideas that readers might have about themselves or the world. She contemplates her body and life as an Irishwoman in her roles as daughter and patient, and in a variety of social and familial roles. Gleeson also explores the female body in pain, in sexuality, and in the struggle for recovery and change both in the Irish context and universally. This courageous example of essayism crosses many borders: the geographical and social, theory and practice, and thinking and creating.Border Poetics De-limited, edited by Johan Schimanski and Stephen Wolfe (2007), examines the role of art and culture in constructing and tracing borders, focusing on narratives and other symbolic forms, and on the important subjective dimension which cultural forms mediate in the public sphere. This article explores how and to what effect the devices proposed by the authors of this collection can be used to relate Gleeson’s essayism to several concepts of border crossing, such as how the border crosser and border-crossing narrative work from a feminist perspective.
Keywords: Sinéad Gleeson; border poetics; non-fiction; illness; gender and politics